Decision Support System For Natural Disaster Aid Recipients Using VIKOR Method: SISTEM PENDUKUNG KEPUTUSAN UNTUK PENERIMA BANTUAN BENCANA ALAM MENGGUNAKAN METODE VIKOR - Lengkong, Salvius Paulus; Komansilan, Reinhard; Akay, Yuri (Universitas Sam Ratulangi, 2023)
Indonesia is a country with a tropical climate which is geographically located around the equator or on the equator. Natural disasters often occur in Indonesia because Indonesia is geographically located on the four plates of the Asian continent, the Australian continent, the Indian Ocean plate and the Pacific Ocean plate. Data from the Central Statistics Agency shows that around 1143 villages/sub-districts were affected by natural disasters in North Sulawesi Province, Indonesia. The city of Manado, which is the capital of North Sulawesi province, has in recent years been hit by natural disasters such as floods and landslides or the dry season. Many victims were affected by this natural disaster. In this research, we succeeded in creating a decision support system for recipients of natural disaster aid using the VIKOR method. Using the VIKOR method can speed up decision making, especially in selecting recipients of natural disaster aid. Apart from that, the use of this system is more objective because the system makes determinations based on criteria and weights determined by the decision maker.